Tubercular dactylitis with discharging sinus in an adult patient. (28th February 2012) - Shantanu, Kumar; Kumar, Santosh; Jain, Sonal
Abstract : Tubercular dactylitis, a term used for tuberculosis of short and tubular bones of hands and feet, rarely shows involvement of the foot. It is more commonly found in children as compared with adults. A 27-year-old male, came with history of discharging sinus over dorsum of great toe of right foot. Clinical assessment led to the suspicion of tuberculosis which was later confirmed by biopsy. This case highlights the importance relying on clinical impression and considering tuberculosis as an aetiology even at unusual sites of involvement.